The Importance of Work-Life Balance Before and During Work from Home After the Covid-19 Pandemic Situation - Muhammad Dimyati Sudja; Kumba Digdowiseiso (Budapest International Research and Critics University, 2022)
Throughout the Covid-19 endemic, many activities were not tried by looking at the face, as a result of which many views of life changed. One of the most noticeable changes is the place of activity. The place of activity is one of the aspects that contribute to the production power of the activity. Not only that, the endemic covid-19 has also changed the activity system from serving in the office to duty from home with the aim of deciding the link between the spread of Covid-19. The intertwined changes require employees to be able to create a work-life balance as a result so that the life of activities and individual lives are not hampered. The purpose of this research is to recognize the importance of work from home and work-life balance to the production power of Covid 19 pacsa activities. The methodology used is a qualitative procedure with a bibliography research analysis method from various bases (daily, novel, internet) through conventional information. This means that researchers use research first with an elastic similar to the base and a bottom reference for improvisation. The results of this research can be concluded that the work-life balance and work from home after Covid 19 are balances in carrying out professional traditions.